PERFORMANCE OF RAINFED MUSTARD UNDER DOUBLE CROPPING SYSTEM AS INFLUENCED BY PRECEDING KHARIF CROP, MULCHING AND N FERTILIZATION ON LIGHT TEXTURED ERODED SOIL OF CENTRAL UTTAR PRADESH - Bhan, Suraj; Kholkhar, R.P.S.; Agrawal, S.K. (Journal of Soil and Water Conservation, 2022)
With a view to enhancing the productivity of rainfed mustand ’Varuna’ under double cropping system on lifht textured eroded soils of Uttar Pradesh, a field experiment was conducted at Soil Conservation Farm of the Chandra Shekhar Azad University of Agriculture and Technology, Kanpuur for 5 consecutive years of 1980-81 to 1984-85. The tregtments comprised 5 Kharif crops viz. Moong K-851, utd T-9, Jowar (Fodder) T8B, Maize T-41 and fallow and 4 moisture conservation practices cum N levels viz control mulching of rice straw @2.5t/ha on the soil surface in between the crop was application of 40kg N/ha and mulching +application of 40 kg N/ha which in all possible combination were compared in a aplit plot design of layout placing Kharif crops in main plots and comination of mulching and N fertilization in sub plots. The five years results showed highest yield, net return and water use efficiency of mustanrd when planted after Unl T-9 followed by Moong K-851 while the crop planted after Jowar (Fooder) gave the poorest performance followed by the crop planted after maize T-44. The yield return and water use efficiency of mustard were improved substantially when rice straw mulch @2.5 t/ha in between the crop rows and 40 N kg/ha at planting were applied,